Efficient hedging in an illiquid market - Kalin, Erik (2011)
Vattenfall hedge its future electricity production in order to decrease fluctuations in the result. Hedging can in a simplified way be described as selling the future electricity deliveries in long-term contracts so that the future price of the delivery becomes fixed. The contracts used are electricity forwards traded at the Nordic electricity market Nord Pool. An imbalance between buyers and sellers can lead to a situation where the forward price not equals the expected spot price. The difference between the forward price and the expected spot price is referred to as the market risk premium. This is the extra premium that market participants are willing to pay to offset risk. Vattenfall’s production portfolio is one of the largest in the Nordic region and the lack of liquidity at Nord Pool’s long-term contracts is therefore a limiting factor in effective risk management. The theory is that partly due to the lower liquidity in the longer contracts, Vattenfall pays an unfavorable risk premium in its long term hedges (i.e. selling the electricity to a discount).